Auxiliary Service Market Model Considering the Participation of Pumped-Storage Power Stations in Peak Shaving - Zhang, Zilong; Cong, Wenbo; Liu, Shizhong; Li, Chenglong; Qi, Shaolong (Frontiers in Energy Research, 2022)
In the context of insufficient system operation flexibility and increasing peaking pressure caused by the large-scale integration of renewable energy into the grid, a market model for peaking auxiliary services involving pumped storage power stations is proposed in this study. First, taking the minimum peak shaving cost as the optimization goal, the peak shaving value of the participating peak shaving units is quantified, and the mathematical model of the peak shaving auxiliary service market is established. Then, considering that the pumped-storage power station has both source-load characteristics, the peak-shaving value of the pumped-storage power station is deeply excavated to share the peak-shaving pressure of thermal power units, and a compensation mechanism for peak ancillary service fees is established. Finally, the 11-machine, 14-node system topology is proposed to simulate the peak-shaving auxiliary service market model proposed in this study, and the effectiveness of the proposed method is verified.